Optimization Design of Cantilever Beam for Cantilever Crane Based on Improved GA - Shufang Wu; Tiexiong Su (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Based on in depth study of optimization design methods, according to analyzing the forces of cantilever beam for Cantilever Crane, with the feature that I-beams used in cantilever beam mostly, combining structural optimization technique with discrete variables with GA, an optimization design method of cantilever beam for Cantilever Crane based on improved GA was proposed for the problems of huge material redundancy and high production cost. Mathematical model and fitness function of the structural optimization with discrete variables were built, optimization design of cantilever beam structure was achieved, the efficiency of this optimization design method was validated and the consumption of steel for production was reduced. This method had a certain guiding significance for engineering application. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4807